Determining the factors and barriers affecting female labor force participation in the Philippines - Tiongco, Marites M. (Animo Repository, 2022)
While the gender gap in the Philippines is slowly closing in terms of wage, labor force participation (LFP) for women have remained much lower than that for men especially in decent work, despite legal and legislative initiatives that are meant to encourage them to enter the labor force. This study investigates how context-specific barriers – legal, social contexts, and norms, may be hampering female LFP. This study conducts a preliminary investigation into these barriers using the Philippine Labor Force Survey. We find that women have lower participation in decent work. Education is associated with greater access to decent work. The same association is found for separated and annulled women, but married women and those with children face a penalty to their LFP, which may be attributed to household duties, family-related work, and higher school enrolment. However, results are sensitive to how decent work is defined, and in an alternative specification, children and married life may encourage the pursuit of stable, higher-paying, tenured type of jobs for women. Equality between husband and wife in terms of education and age may lead to higher participation in decent work as well.